Applications = code + markup : a guide to the Microsoft Windows presentation foundation. - Petzold, Charles, 1953- (Redmond : Microsoft, 2006)
In this book, Windows programming legend Charles Petzold covers in parallel the two interfaces that make up the Windows Presentation Foundation (WPF). From the outset, the reader can shift focus seamlessly between Extensible Application Markup Language (XAML) and C# to see them as flip sides of the same processes. Beginning in the first chapter, Petzold presents the general syntax of the XAML and corresponding programming code with numerous illuminating examples on how the two correspond and interrelate. The book builds on this base, providing the classic Petzold Windows user interface (UI) treatment, to show Windows developers how to create next-generation interfaces for their applications.